Effects of high-performance human resource practices in the education sector: The mediational model - Yang, Cunbo; Yasmin, Fakhra (Frontiers in Psychology, 2022)
(HPHRPs) and outcomes, this study examines the mediating roles of person job fit and person organisation fit by using the congruence theory. Through a survey questionnaire, data from 296 people who work at educational institutions in China were gathered. Results demonstrate that the association between HPHRPs and outcomes is mediated by both person job fit (PJ fit) and person organisation fit (PO fit). The results indicate theoretical implications and suggest that HPHRPs are important antecedent that builds congruence among employees’ values and goals to organizational values and goals as well as their job goals that in turn avoid employees to be stressed and have leaving intentions. The current study adds to the extant literature on education and HPHRPs by identifying PJ fit and PO fit as mechanisms through which HPHRPs demonstrate their authority on employee outcomes. The managerial implications along with limitations and directions for future studies are included in detail at the end.